Migración y crisis familiar en niños, niñas y adolescentes de la parroquia de Uzhcurrumi del cantón Pasaje, año 2012 - Uzhca Vera, Byron Javier (2012)
A process of research based on the hypothetical-deductive processes is proposed, subject to the scientific method that guides the systematization of the contents of the diagnosis from an analytical empirical paradigm, in whose structure the problem is studied, it is described, it fixes its Location and is justified.